The Roles of Microtubules and Membrane Tension in Axonal Beading, Retraction, and Atrophy - Bernal-Valenzuela, R (Biophysical Society, 2019)
Axonal beading, or the formation of a series of swellings along the axon, and retraction are commonly observed shape transformations that precede axonal atrophy in Alzheimer s disease, Parkinson s disease, and other neurodegenerative conditions. The mechanisms driving these morphological transformations are poorly understood. Here, we report controlled experiments that can induce either beading or retraction and follow the time evolution of these responses. By making quantitative analysis of the shape modes under different conditions, measurement of membrane tension, and using theoretical considerations, we argue that membrane tension is the main driving force that pushes cytosol out of the axon when microtubules are degraded, causing axonal thinning. Under pharmacological perturbation, atrophy is always retrograde, and this is set by a gradient in the microtubule stability. The nature of microtubule depolymerization dictates the type of shape transformation, vis-à-vis beading or retraction. Elucidating the mechanisms of these shape transformations may facilitate development of strategies to prevent or arrest axonal atrophy due to neurodegenerative conditions. © 2019 Biophysical Society